Barremian bivalves from the Huitrín formation, west-central Argentina: Taxonomy and paleoecology of a restricted marine association - Lazo, Dario Gustavo (2011)
The Cretaceous Huitrín Formation in west-central Argentina records the final connection of the Neuquén Basin to the Pacific Ocean. This formation is comprised of a variety of continental to marginal-marine sediments deposited behind an Andean volcanic arc under warm, arid paleoclimatic conditions. Here we focus on a bivalve fauna from carbonate ramp deposits within the Barremian La Tosca Member of the Huitrín Formation. This fauna is very abundant and widely distributed within the basin but, surprisingly, it has not yet been studied in detail. In addition, paleoenvironmental affinities remain unresolved, with the fauna variously interpreted as having freshwater, brackish, and marine affinities. We studied the fauna's taxonomy and paleoecology based on more than 500 specimens collected at ten fossil localities in combination with new field observations. The bivalve assemblage was recorded from middle to outer carbonate ramp deposits and is composed of five taxa of marine affinity: Phelopteria huitriniana n. sp., Isognomon cf. I. nanus (Behrendsen), Placunopsis? pichi n. sp., Anthonya jarai n. sp., and Argenticyprina mulensis n. gen. n. sp.; the first three may be regarded as eurytopic and/or opportunistic. Reduced diversity, low evenness, overall small size (length <4 cm), thin shells, eurytopic or opportunistic life strategies, and high endemism point to a restricted marine setting for the La Tosca Member. The most important limiting factors likely were low primary productivity and fluctuating salinity and temperature, as conditions inferred for the unit include high evaporation rates combined with low continental runoff and reduced rainfall. Thick evaporite deposits below and above La Tosca Member and thin intercalated gypsum beds support a restricted, hypersaline setting.